Fiber resin-based composite material with interlayer wave lock structure and preparation method of fiber resin-based composite material
By combining unidirectional fiber resin cloth and fabric fiber resin cloth with hot pressing, an interlayer wave lock structure is formed, which solves the problem of insufficient resistance of fiber resin-based composite materials under impact and compression loads, and significantly improves its impact and resistance. Compression performance.
Patent Information
- Application Number
- CN202411426015.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
AI Technical Summary
When fiber resin-based composite materials are affected by interlayer layering, normal impact and lateral shear, the interlayer bonding strength is low, the impact resistance is poor and the compressive strength is insufficient, resulting in easy structure damage and increasing unpredictable risks. .
Using hot press laminated and bonded unidirectional fiber resin cloth and fabric fiber resin cloth, the interlayer wave lock structure is formed, and the fiber braiding and conical nail structure of the fabric fiber resin cloth is used to enhance the surface joint strength, and form a cladding lock. Or nail lock structure to enhance impact and compression resistance.
Effectively improve the impact and compression resistance of fiber resin-based composite materials, reduce interlayer layering and damage, improve the shear strength and compression resistance of composite materials, and significantly improve its strength under impact and compression loads. .
Smart Images

Figure CN119305265A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber resin-based composite materials, and in particular to a fiber resin-based composite material with an interlayer wave-lock structure and a preparation method thereof. Background Art
[0002] Fiber resin-based composite materials can be used as structural materials to carry loads, and as functional materials to meet some functional requirements. They have low density, high specific strength, high specific modulus, fatigue resistance, corrosion resistance and other excellent properties, and are widely used in aerospace, automobile manufacturing and other fields. For example, carbon fiber resin-based composite materials have gradually extended from the application of secondary load-bearing components such as car bodies, interior and exterior decorations to key load-bearing components such as chassis, bearings, and engines, which can not only improve their structural strength, but also reduce the overall weight of the car while ensuring strength, effectively reducing energy consumption.
[0003] Although fiber-resin-based composite materials have many advantages mentioned above, they are easily affected by factors such as interlayer delamination, normal impact and transverse shear, resulting in problems such as low interlayer bonding strength, poor impact resistance and insufficient compressive strength. In particular, when subjected to impact loads, they are prone to delamination damage, greatly reducing the strength of fiber-resin-based composite materials and bringing unpredictable risks to the structure of fiber-resin-based composite component parts. Summary of the invention
[0004] The purpose of the present invention is to provide a fiber resin-based composite material with an interlayer wave-lock structure and a preparation method thereof. The composite material provided by the present invention has good impact resistance and compression resistance and is not prone to delamination damage when subjected to loads such as impact and compression.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a fiber resin-based composite material with an interlayer wave-lock structure, comprising a plurality of layers of unidirectional fiber resin cloth and a plurality of layers of woven fiber resin cloth bonded by hot pressing lamination; the resins in the unidirectional fiber resin cloth and the woven fiber resin cloth are the same; the unidirectional fiber resin cloth and the woven fiber resin cloth are formed by hot pressing impregnation and hot pressing curing of a unidirectional fiber resin-based prepreg cloth and a woven fiber resin-based prepreg cloth in sequence.
[0007] Preferably, each layer of the textile fiber resin cloth independently: no cone nails are arranged at the interweaving points of the warp yarns and the weft yarns, or cone nails are arranged at some of the interweaving points, or cone nails are arranged at all the interweaving points.
[0008] Preferably, the cone nails are composed of a fiber-resin composite material having the same resin matrix and the same fibers as the textile fiber resin cloth.
[0009] Preferably, the height of the cone nail is 0.1-1 mm, and the length at the maximum cross-section position is 0.1-0.5 mm.
[0010] Preferably, the cone nails are arranged unidirectionally or bidirectionally.
[0011] Preferably, the thickness of a single-layer woven fiber resin cloth is independently 0.25 to 0.64 mm, and the thickness of a single-layer unidirectional fiber resin cloth is independently 0.02 to 0.25 mm.
[0012] Preferably, the fibers in the unidirectional fiber resin cloth and the woven fiber resin cloth are independently carbon fibers, basalt fibers, glass fibers, aramid fibers or ultra-high molecular weight polyethylene fibers.
[0013] Preferably, the corresponding plies of the fiber resin-based composite material are: [UD1 / UD2 / WF / UD3 / UD4], [UD1 / WF / UD2 / WF / UD3], [WF / UD1 / WF / UD2 / WF] or [WF / WF / UD1 / WF / WF];
[0014] Among them, from top to bottom, each layer is separated by " / ", and all layers are enclosed by "[]"; UD1~UD4 independently represent a laminate composed of 4 to 6 layers of unidirectional fiber resin cloth, and the ply of the unidirectional fiber resin cloth is [45 / 0 / -45 / 90], [45 / 0 / -45 / 90 / 45] or [-45 / 45 / 0 / -45 / 90 / -45]; WF represents a layer of woven fiber resin cloth, and its ply is [(0,90)] or [(±45)], wherein [(0,90)] means that the ply angle of the woven fiber resin cloth is the same as that of the 0° unidirectional fiber resin cloth, and [(±45)] means that the ply angle of the woven fiber resin cloth and the 0° unidirectional fiber resin cloth differs by 45°.
[0015] The present invention provides a method for preparing the fiber resin-based composite material with an interlayer wave-locking structure as described in the above scheme, comprising the following steps:
[0016] The unidirectional fiber resin-based prepreg cloth and the textile fiber resin-based prepreg cloth are stacked according to a preset layer to obtain a laminated prepreg;
[0017] The laminated prepregs are sequentially subjected to hot-press impregnation and hot-press curing to obtain the fiber resin-based composite material with an interlayer wave-locking structure.
[0018] Preferably, when the fiber resin-based composite material with an interlayer wave-lock structure contains cone nails, before stacking, the cone nails are pre-arranged at the interweaving points of the warp yarns and the weft yarns of the textile fiber resin-based prepreg cloth.
[0019] The present invention provides a fiber resin-based composite material with an interlayer wave-lock structure, comprising a plurality of layers of unidirectional fiber resin cloth and a plurality of layers of woven fiber resin cloth bonded by hot pressing lamination; the resins in the unidirectional fiber resin cloth and the woven fiber resin cloth are the same; the unidirectional fiber resin cloth and the woven fiber resin cloth are formed by hot pressing impregnation and hot pressing curing of a unidirectional fiber resin-based prepreg cloth and a woven fiber resin-based prepreg cloth in sequence.
[0020] Traditional fiber resin composite materials are composed of unidirectional fiber resin cloth according to a specific plying order and angle, and the layers are easy to delaminate; the present invention introduces a fabric fiber resin cloth, which has a bulge formed by fiber weaving. After hot pressing, an interface wave lock effect can be formed in the unidirectional fiber resin cloth, so that the fibers form a surface bite enhancement effect of a locking structure, which prevents relative sliding in the shear direction, creates an obstacle to relative movement, improves the bonding strength between layers, increases the contact area between layers, and provides a stable connection and anti-movement effect. Therefore, the present invention can reduce the degree of damage to the composite material, effectively improve the impact resistance and compression resistance in impact compression loads, and at the same time, the interlayer shear strength of the bionic wave lock structure composite material is improved, which can enhance the degree of bonding between the composite material layers and reduce the delamination and damage problems of the composite material. The resin in the unidirectional fiber resin cloth and the fabric fiber resin cloth of the present invention is the same, which can reduce other chemical reactions between different resins during the curing process, affecting the mechanical properties of the overall composite material.
[0021] Furthermore, the present invention arranges cone nails at some or all of the interweaving points of the warp and weft yarns of the textile fiber resin cloth, and on the basis of forming the surface interlocking enhancement effect of the wrapping structure, it can further form the point interlocking enhancement of the nail locking structure (both the wrapping structure and the nail locking structure belong to the wave locking structure), further enhance the interlayer bonding strength, give the composite material better impact resistance and compression resistance, and reduce the delamination and damage of the composite material under impact compression loads. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the wave-lock structure laminated prepreg of Examples 1-2;
[0023] Figure 2 It is a schematic diagram of a hot pressing forming device;
[0024] Figure 3 This is a schematic diagram of the process of preparing the bionic nail locking plate of Example 2;
[0025] Figure 4 The morphology comparison diagram of the impact front, the cross section at the impact indentation and the back of the traditional board, the bionic package lock board and the bionic nail lock board during the low-impact test;
[0026] Figure 5Comparison of defect areas of the impact front (left) and the cross section at the impact indentation (right) of the traditional plate, bionic package locking plate and bionic nail locking plate after low-speed impact by ultrasonic C scanning;
[0027] Figure 6 Comparison of the morphology of the front side of impact, the cross section at the impact indentation, and the back side of the traditional plate, bionic package locking plate, and bionic nail locking plate during the post-impact compression test;
[0028] Figure 7 The comparison chart of impact strength and residual compression strength of traditional plate, bionic package locking plate and bionic nail locking plate;
[0029] Figure 8 Comparison of the topography of the front, hole cross section and end face of the traditional plate, bionic package locking plate and bionic nail locking plate during the open hole compression test;
[0030] Fig. 9 The comparison chart of the opening compression strength and interlaminar shear strength of the traditional board, the bionic package locking board and the bionic nail locking board;
[0031] Figures 1-2 Middle: 1- unidirectional fiber resin-based prepreg cloth with a 45° ply angle; 2- unidirectional fiber resin-based prepreg cloth with a 0° ply angle; 3- unidirectional fiber resin-based prepreg cloth with a -45° ply angle; 4- unidirectional fiber resin-based prepreg cloth with a 90° ply angle; 5- 3K plain weave fabric prepreg cloth; 6- 3K plain weave fabric prepreg cloth with pre-embedded cone nails; 7- upper pressing plate; 8- upper mold; 9- bionic package locking structure composite material; 10- release agent; 11- lower mold; 12- lower pressing plate. DETAILED DESCRIPTION
[0032] The present invention provides a fiber resin-based composite material with an interlayer wave-lock structure, comprising a plurality of layers of unidirectional fiber resin cloth and a plurality of layers of woven fiber resin cloth bonded by hot pressing lamination; the resins in the unidirectional fiber resin cloth and the woven fiber resin cloth are the same; the unidirectional fiber resin cloth and the woven fiber resin cloth are formed by hot pressing impregnation and hot pressing curing of a unidirectional fiber resin-based prepreg cloth and a woven fiber resin-based prepreg cloth in sequence.
[0033] In the present invention, the unidirectional fiber resin-based prepreg cloth preferably uses a thermosetting epoxy resin as a matrix, and the curing degree of the resin matrix is preferably 20-40%, specifically 20%, 30%, or 40%. The present invention has no special requirements for the content of the resin matrix and the fiber in the unidirectional fiber resin-based prepreg cloth, and any unidirectional fiber resin-based prepreg cloth known in the art can be used.
[0034] In the present invention, the resin matrix of the textile fiber resin-based prepreg cloth is the same as the resin matrix of the unidirectional fiber resin-based prepreg cloth, and the curing degree of the resin matrix is preferably 30-50%, specifically 30%, 40% or 50%. The present invention has no special requirements for the thermosetting epoxy resin, and any thermosetting epoxy resin known in the art can be used. In an embodiment of the present invention, the thermosetting epoxy resin matrix is obtained by mixing E44 epoxy resin and polyamide curing agent, and the mass ratio of E44 epoxy resin to polyamide curing agent is 3:1. The present invention has no special requirements for the content of the resin matrix and fiber in the textile fiber resin-based prepreg cloth, and any textile fiber resin-based prepreg cloth known in the art can be used.
[0035] In the present invention, the fibers in the unidirectional fiber resin cloth and the woven fiber resin cloth are preferably independently carbon fibers, basalt fibers, glass fibers, aramid fibers or ultra-high molecular weight polyethylene fibers.
[0036] The present invention has no special requirements on the specifications of the fibers in the unidirectional fiber resin cloth, and any well-known specifications are acceptable. In the present invention, the weaving form of the fabric fiber resin cloth is preferably plain, twill or satin; the fiber tows of the fabric fiber resin cloth are preferably 3K, 12K or 24K.
[0037] In the present invention, the thickness of a single-layer woven fiber resin cloth is independently preferably 0.25-0.64 mm; in a specific embodiment, it can be 0.25 mm, 0.30 mm, 0.35 mm, 0.40 mm, 0.45 mm, 0.50 mm, 0.60 mm or 0.64 mm, which are not listed here. The thickness of a single-layer unidirectional fiber resin cloth is independently preferably 0.02-0.25 mm, in a specific embodiment, it can be 0.02 mm, 0.05 mm, 0.10 mm, 0.20 mm or 0.25 mm, which are not listed here. The present invention has no special requirements for the total number of layers of the woven fiber resin cloth and the unidirectional fiber resin cloth, and the appropriate total number of layers can be selected according to the target thickness and the single-layer thickness.
[0038] In the present invention, the fabric fiber resin cloth can be located on the surface and / or middle layer of the fiber resin matrix composite material. The present invention does not specifically limit the number and position of the fabric fiber resin cloth. The present invention does not specifically require the ply angle of each layer, which is determined according to the target design.
[0039] As a preferred solution, the corresponding plies of the fiber resin-based composite material are: [UD1 / UD2 / WF / UD3 / UD4], [UD1 / WF / UD2 / WF / UD3], [WF / UD1 / WF / UD2 / WF] or [WF / WF / UD1 / WF / WF];
[0040] Among them, from top to bottom, each layer is separated by " / ", and all layers are enclosed by "[]"; UD1~UD4 independently represent a laminate composed of 4 to 6 layers of unidirectional fiber resin cloth, and the ply of the unidirectional fiber resin cloth is [45 / 0 / -45 / 90], [45 / 0 / -45 / 90 / 45] or [-45 / 45 / 0 / -45 / 90 / -45]; WF represents a layer of woven fiber resin cloth, and its ply is [(0,90)] or [(±45)], wherein [(0,90)] means that the ply angle of the woven fiber resin cloth is the same as that of the 0° unidirectional fiber resin cloth, and [(±45)] means that the ply angle of the woven fiber resin cloth and the 0° unidirectional fiber resin cloth differs by 45°.
[0041] In the present invention, each layer of fabric fiber resin cloth independently: no cone nails are arranged at the interweaving points of the warp and weft yarns, or cone nails are arranged at some of the interweaving points, or cone nails are arranged at all of the interweaving points. For example, in Example 1, cone nails are not arranged at all fabric fiber resin cloths, and only a wrapping structure is formed. For another example, when the fiber resin-based composite material with an interlayer wave lock structure contains two layers of fabric fiber resin cloth, one layer may not be arranged with cone nails, and the other layer of fabric fiber resin cloth may be partially or fully arranged with cone nails at the interweaving points of the warp and weft yarns; it is also possible to arrange cone nails at only some of the interweaving points of the two layers of fabric fiber resin cloth; it is also possible to arrange cone nails at all of the interweaving points of the two layers of fabric fiber resin cloth; it is also possible to arrange cone nails at only some of the interweaving points of one layer, and arrange cone nails at all of the interweaving points of the other layer.
[0042] In the present invention, the cone nail is preferably composed of a fiber-resin composite material having the same resin matrix and the same fibers as the woven fiber-resin cloth.
[0043] In the present invention, the shape of the cone nail is preferably one or more of a circular cone, a diamond cone, a triangle, a teardrop shape and a thin rod shape; the height of the cone nail is preferably 0.1-1 mm, and the length at the maximum cross-sectional position is preferably 0.1-0.5 mm; in a specific embodiment, the height of the cone nail can be 0.1 mm, 0.3 mm, 0.5 mm, 0.7 mm or 1.0 mm, and the length of the cone nail at the maximum cross-sectional position can be 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm or 0.5 mm, which are not enumerated here.
[0044] In the present invention, the cone nails are preferably arranged unidirectionally or bidirectionally; when the cone nails are arranged unidirectionally, the tips can be facing upward or downward; when the cone nails are arranged bidirectionally, they can be arranged regularly or irregularly, preferably regularly, and more preferably, the cone nails of adjacent interlacing points are distributed one up (with the tips facing upward) and one down (with the tips facing downward).
[0045] In the present invention, by arranging cone nails at some or all of the interlacing points of the warp and weft of the textile fiber resin cloth, on the basis of forming the surface bite enhancement effect of the wrap-lock structure, the point bite enhancement of the nail-lock structure can be further formed, the interlayer bonding strength is further enhanced, the composite material is given better impact resistance and compression resistance, and the delamination and damage of the composite material under impact compression load is reduced.
[0046] The present invention provides a method for preparing the fiber resin-based composite material with an interlayer wave-locking structure as described in the above scheme, comprising the following steps:
[0047] The unidirectional fiber resin-based prepreg cloth and the textile fiber resin-based prepreg cloth are stacked according to a preset layer to obtain a laminated prepreg;
[0048] The laminated prepregs are sequentially subjected to hot-press impregnation and hot-press curing to obtain the fiber resin-based composite material with an interlayer wave-locking structure.
[0049] In the present invention, when the fiber resin-based composite material with an interlayer wave-lock structure contains cone nails, the present invention pre-arranges the cone nails at the interweaving points of the warp yarns and the weft yarns of the textile fiber resin-based prepreg cloth.
[0050] In the present invention, the unidirectional fiber resin-based prepreg cloth and the textile fiber resin-based prepreg cloth are preferably cut into target sizes before stacking.
[0051] The present invention has no special requirements for the stacking process, and the stacking process well known in the art can be used. Specifically, a suitable mold is selected according to the shape of the fiber resin-based composite material (for example, it can be a flat part or a curved part), and the mold release wax is evenly applied in the mold. Then, the layers of prepreg to be stacked are stacked in the lower mold according to the designed stacking order and stacking angle, and the upper mold is covered.
[0052] In the present invention, the material of the mold is preferably aluminum-based material.
[0053] The present invention has no special requirements for the conditions of hot press impregnation and hot press curing. According to the type of prepreg, the hot press curing conditions known in the art can be selected. In the embodiment of the present invention, for the unidirectional fiber resin-based prepreg cloth is USN 12500 (purchased from Guangwei Composite Materials Co., Ltd.), the fabric fiber resin-based prepreg cloth is 3K plain fabric prepreg cloth (purchased from Guangwei Composite Materials Co., Ltd., W-3011), the temperature of the hot press impregnation is 80°C, the extrusion pressure is 0.65MPa, and the holding time is 30min; the temperature of the hot press curing is 120°C, the extrusion pressure is 0.65MPa, and the holding time is 60min.
[0054] The present invention has no special requirements for the implementation process of the hot press impregnation and hot press curing, and the implementation process well known in the art can be used. In the embodiment of the present invention, specifically: the stacked prepreg is placed between the upper mold and the lower mold coated with a release agent, and the upper and lower pressing plates are hydraulically lifted and moved to first perform hot press impregnation, and then hot press curing. After the hot press curing is completed, the normal pressure is slowly restored, and the temperature is lowered to below 60°C for demoulding to obtain the fiber resin-based composite material with an interlayer wave-locking structure.
[0055] The fiber resin-based composite material with an interlayer wave-locking structure and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0056] Example 1
[0057] like Figure 1 As shown in the middle left side, unidirectional fiber resin-based prepreg cloths 1 to 4 (purchased from Guangwei Composite Materials Co., Ltd., USN 12500) are selected, and thermosetting epoxy resin is used as the matrix. E44 epoxy resin and polyamide curing agent are evenly mixed to obtain the obtained material. The mass ratio of E44 epoxy resin to polyamide curing agent is 3:1, the matrix resin curing degree is 20-30% (the range value provided by the merchant), and the single layer thickness is 0.125mm; 3K plain weave fabric prepreg cloth 5 (purchased from Guangwei Composite Materials Co., Ltd., W-3011) is selected, the matrix is the same as the unidirectional prepreg cloth, the matrix resin curing degree is 30-40% (the range value provided by the merchant), and the single layer thickness is 0.25mm; the fiber reinforcement material is selected from carbon fiber; the prepreg cloth is cut into side lengths Rectangular sheets of 150×100 mm (for impact strength test) and 300×36 mm (for open hole compression strength test) are cut into 18 sheets (referring to the total number of prepreg sheets used in each test), of which 16 sheets are unidirectional fiber resin prepreg cloths and 2 sheets are 3K plain weave fabric prepreg cloths; prepreg cloths with a ply angle of 45° are stacked in sequence, and the laying method is [45 / 0 / -45 / 90 / 45 / (0,90) / -45 / 45 / 0 / -45 / 90 / -45 / (0,90) / 45 / 90 / -45 / 0 / 45] to obtain laminated prepreg; then according to Figure 2 , a milling mold is used, and an aluminum-based material is selected. The laminated prepreg is placed between an upper mold 8 and a lower mold 11 coated with a release agent 10; through the hydraulic lifting and moving of the upper pressing plate 7 and the lower pressing plate 12, hot pressing impregnation is first performed, the temperature of the curing device is 80°C, the extrusion pressure provided is 0.65MPa, and the pressure is maintained for 30 minutes; then hot pressing curing is performed, the temperature of the curing device is 120°C, the extrusion pressure provided is 0.65MPa, and the pressure is maintained for 60 minutes; after the hot pressing curing is completed, the normal pressure is slowly restored, and the temperature is lowered to below 60°C for demolding to obtain a bionic locking structure composite material 9 (bionic locking plate).
[0058] Example 2
[0059] according to Figure 3 The process shown proceeds as follows:
[0060] Unidirectional fiber resin-based prepreg cloths 1-4 are selected, and thermosetting epoxy resin is used as the matrix. E44 epoxy resin and polyamide curing agent are uniformly mixed to obtain the obtained material. The mass ratio of E44 epoxy resin to polyamide curing agent is 3:1, the matrix resin curing degree is 20-30%, and the single layer thickness is 0.125 mm. A 3K plain weave fabric prepreg cloth 6 with pre-embedded cone nails is selected. The matrix is the same as the unidirectional prepreg cloth, the matrix resin curing degree is 30%-40%, and the single layer thickness is 0.25 mm. The cone nails are circular cones with a diameter of 0.1 mm and a height of 0.5 mm, and the cone nails are pre-embedded in bidirectional distribution in the warp and weft interlacing of the fabric prepreg, and the adjacent interlacing points are kept in an upper (tip facing up) and a lower (tip facing down) distribution. ; The fiber reinforcement material is selected from carbon fiber; the prepreg cloth is cut into rectangular pieces with side lengths of 150×100 mm (for impact strength test) and 300×36 mm (for open hole compression strength test), and the number of cut pieces is 18 pieces (referring to the total number of prepreg pieces used in each group of tests), of which 16 pieces are unidirectional fiber resin prepreg cloths and 2 pieces are 3K plain weave fabric prepreg cloths with embedded cone nails; the prepreg cloths with a ply angle of 45° are stacked in sequence, and the laying method is [45 / 0 / -45 / 90 / 45 / (0,90) / -45 / 45 / 0 / -45 / 90 / -45 / (0,90) / 45 / 90 / -45 / 0 / 45] to obtain a laminated prepreg (such as Figure 1 As shown on the right side of the figure, ); the milling mold is made of aluminum-based material, and the laminated prepreg is placed between the upper mold and the lower mold coated with a release agent; the upper and lower pressing plates are hydraulically lifted and moved, and hot pressing impregnation is first performed, the temperature of the curing device is 80°C, the extrusion pressure provided is 0.55MPa, and the pressure is maintained for 30 minutes; then hot pressing curing is performed, the temperature of the curing device is 120°C, the extrusion pressure provided is 0.55MPa, and the pressure is maintained for 60 minutes; after the hot pressing curing is completed, the normal pressure is slowly restored, and the temperature is lowered to below 60°C for demolding to obtain a bionic nail locking structure composite material (bionic nail locking plate).
[0061] Comparative Example 1
[0062] Preparation of supplementary traditional composite materials: unidirectional fiber resin-based prepreg cloths 1 to 4 are selected, thermosetting epoxy resin is used as the matrix, E44 epoxy resin and polyamide curing agent are uniformly mixed to obtain the obtained material, the mass ratio of E44 epoxy resin to polyamide curing agent is 3:1, the matrix resin curing degree is 20-30%, and the single layer thickness is 0.125 mm; the fiber reinforcement material is selected from carbon fiber; the prepreg cloth is cut into rectangular pieces with side lengths of 150×100 mm and 300×36 mm, respectively, and the number of cuts is 20; the prepreg cloths with a ply angle of 45° are stacked in sequence, and the laying method is [45 / 0 / -45 / 90 / 45 / 0 / -45 / 90 / 45 / 0 / -45 / 90 / 90 / -45 / 0 / 45 / 90 / -45 / 0 / 45] to obtain a laminated prepreg; a milling mold is made of aluminum-based material, and the laminated prepreg is placed between an upper mold and a lower mold coated with a release agent; hot pressing impregnation is first performed by hydraulically lifting and lowering the upper and lower pressing plates, the temperature of the curing device is 80°C, the extrusion pressure provided is 0.55MPa, and the pressure is maintained for 30 minutes; hot pressing curing is then performed, the temperature of the curing device is 120°C, the extrusion pressure provided is 0.55MPa, and the pressure is maintained for 60 minutes; after the hot pressing curing is completed, normal pressure is slowly restored, the temperature is lowered to below 60°C for demoulding to obtain a traditional composite laminate (traditional plate).
[0063] Performance Test:
[0064] The international test standard for aviation composites ASTM / D7136 / D7137 was used to test the low-speed impact resistance of the composite panels of the embodiment and the comparative example, and ASTM / D6484 was used to test the open-hole compression performance of the composite panels. Figures 4 to 9 .
[0065] Figure 4 The morphology comparison diagram of the impact front, the cross section at the impact indentation and the back of the traditional plate, bionic package locking plate and bionic nail locking plate during the low-impact test. The damage degree of the composite plate is analyzed by comparing the diameter and depth of the front impact indentation, the cross-sectional crack failure mode and the extension range of the back crack. The smaller the diameter and depth, the smaller the damage. Figure 5 Comparison of defect areas of the impact front (left) and the cross section at the impact indentation (right) of the traditional plate, bionic package locking plate and bionic nail locking plate after low-speed impact by ultrasonic C scanning. The smaller the defect area, the smaller the damage. Figure 6 The morphology comparison diagrams of the left side, front side, and right side of the traditional plate, bionic package locking plate, and bionic nail locking plate after impact compression are shown. The damage degree of the composite plate is analyzed by comparing the crack extension range at the front impact indentation and the cross-sectional crack failure mode. The smaller the crack, the smaller the damage. Figure 7 The comparison chart of impact strength and residual compression strength of traditional plate, bionic package locking plate and bionic nail locking plate; Figure 8This is a comparison of the morphologies of the front, hole section and end faces of the traditional plate, bionic wrapped locking plate and bionic nail locked plate during the open hole compression test. The damage degree of the composite plate is analyzed by comparing the size of the crack extension range on the front, the warping accumulation size of the hole section and the size of the crack extension range on the end face. The smaller the size, the less damage. Fig. 9 This is a comparison chart of the opening compression strength and interlaminar shear strength of traditional panels, bionic wrapped locking panels and bionic nail locked panels.
[0066] Figures 4 to 9 The test results show that the bionic locking structure composite material of Example 1 can reduce the damage degree of the composite material, effectively improve the impact resistance in impact collision, and the residual compression strength is 6.6% higher than that of the traditional board. Due to the existence of the locking structure, the open hole compression strength and interlaminar shear strength of the locking board are respectively increased by 5.9% and 11.1% compared with the traditional board of Comparative Example 1.
[0067] The bionic nail-locking structure composite material of Example 2 can effectively prevent interlayer delamination and avoid overall damage. The residual compressive strength is increased by 12.3% compared with the traditional board; the impact defect area of the nail-locking board is reduced by 82.2% compared with the traditional board (Comparative Example 1) with the same process. Figure 5 The opening compression strength and interlaminar shear strength of the nail-locked board are increased by 8.9% and 16.4% respectively compared with the traditional board.
[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A fiber resin-based composite material with an interlayer wave-lock structure, comprising a plurality of layers of unidirectional fiber resin cloth and a plurality of layers of woven fiber resin cloth bonded by hot pressing lamination; the resins in the unidirectional fiber resin cloth and the woven fiber resin cloth are the same; the unidirectional fiber resin cloth and the woven fiber resin cloth are formed by hot pressing impregnation and hot pressing curing of a unidirectional fiber resin-based prepreg cloth and a woven fiber resin-based prepreg cloth in sequence.
2. The fiber resin-based composite material according to claim 1, characterized in that: Each layer of textile fiber resin cloth is independently: no cone nails are arranged at the interweaving points of the warp yarns and the weft yarns, or cone nails are arranged at some of the interweaving points, or cone nails are arranged at all the interweaving points.
3. The fiber resin-based composite material according to claim 2, characterized in that: The cone nail is composed of a fiber-resin composite material having the same resin matrix and the same fibers as the textile fiber resin cloth.
4. The fiber resin-based composite material according to claim 2 or 3, characterized in that: The height of the cone nail is 0.1-1 mm, and the length at the maximum cross-section position is 0.1-0.5 mm.
5. The fiber resin-based composite material according to claim 2 or 3, characterized in that: The cone nails are arranged in one direction or in two directions.
6. The fiber resin-based composite material according to claim 1 or 2, characterized in that: The thickness of the single-layer woven fiber resin cloth is independently 0.25 to 0.64 mm, and the thickness of the single-layer unidirectional fiber resin cloth is independently 0.02 to 0.25 mm.
7. The fiber resin-based composite material according to claim 1, characterized in that: The fibers in the unidirectional fiber resin cloth and the woven fiber resin cloth are independently carbon fibers, basalt fibers, glass fibers, aramid fibers or ultra-high molecular weight polyethylene fibers.
8. The fiber resin-based composite material according to claim 1, characterized in that: The corresponding plies of the fiber resin-based composite material are: [UD1 / UD2 / WF / UD3 / UD4], [UD1 / WF / UD2 / WF / UD3], [WF / UD1 / WF / UD2 / WF] or [WF / WF / UD1 / WF / WF]; Among them, from top to bottom, each layer is separated by " / ", and all layers are enclosed by "[]"; UD1~UD4 independently represent a laminate composed of 4 to 6 layers of unidirectional fiber resin cloth, and the ply of the unidirectional fiber resin cloth is [45 / 0 / -45 / 90], [45 / 0 / -45 / 90 / 45] or [-45 / 45 / 0 / -45 / 90 / -45]; WF represents a layer of woven fiber resin cloth, and its ply is [(0,90)] or [(±45)], wherein [(0,90)] means that the ply angle of the woven fiber resin cloth is the same as that of the 0° unidirectional fiber resin cloth, and [(±45)] means that the ply angle of the woven fiber resin cloth and the 0° unidirectional fiber resin cloth differs by 45°.
9. The method for preparing the fiber resin-based composite material having an interlayer wave-locking structure according to any one of claims 1 to 8, characterized in that: The following steps are involved: The unidirectional fiber resin-based prepreg cloth and the textile fiber resin-based prepreg cloth are stacked according to a preset layer to obtain a laminated prepreg; The laminated prepregs are sequentially subjected to hot-press impregnation and hot-press curing to obtain the fiber resin-based composite material with an interlayer wave-locking structure.
10. The preparation method according to claim 9, characterized in that: When the fiber resin-based composite material with an interlayer wave-lock structure contains cone nails, before stacking, the cone nails are pre-arranged at the interweaving points of the warp yarns and the weft yarns of the textile fiber resin-based prepreg cloth.
Citation Information
Patent Citations
Method of manufacturing composite ring piece
CN113858650A
Composite plate for a shoe
KR100607260B1
Cited By
Continuous fiber reinforced composite material, preparation method and pultrusion insulation support plate
CN120422521A
Impact-resistant sandwich composite material laminated plate imitating giant termite multi-layer structure and preparation method of impact-resistant sandwich composite material laminated plate imitating giant termite multi-layer structure
CN121083999A
An impact-resistant sandwich composite laminate imitating the multi-layer structure of dolichoderus ants and a preparation method thereof
CN121083999B